George Frideric Handel : a life with friends - Harris, Ellen T. (New York : W. W. Norton & Company, 2014)
During his lifetime, the sounds of Handel's music reached from court to theater, echoed in cathedrals, and filled crowded taverns, but the man himself - known to most as the composer of Messiah - is a bit of a mystery. Though he took meticulous care of his musical manuscripts and even provided for their preservation on his death, very little of an intimate nature survives. One document - Handel's will - offers us a narrow window into his personal life. In it, he remembers not only family and close colleagues but also neighborhood friends. In search of the private man behind the public figure, Ellen T. Harris has spent years tracking down the letters, diaries, personal accounts, legal cases, and other documents connected to these bequests. The result is a tightly woven tapestry of London in the first half of the eighteenth century, one that interlaces vibrant descriptions of Handel's music with stories of loyalty, cunning, and betrayal. With this wholly new approach, Harris has achieved something greater than biography. Layering the interconnecting stories of Handel's friends like the subjects and countersubjects of a fugue, Harris introduces us to an ambitious, shrewd, generous, brilliant, and flawed man, hiding in full view behind his public persona.
Introductions : Handel and his friends -- Before London -- Politics, patronage, and pension -- Commerce and trade -- Music at home -- Marriage, wealth, and social status -- Ambition, law, and friendship -- Making and collecting -- Religion and charity -- Sickness and death -- Wills and legacies.
Includes bibliographical references (pages 391-409), discography (pages 381-387) and index.
Keywords: Handel, George Frideric, -- 1685-1759.; Composers -- Biography